Effect of Reactor Temperature on Pyrolysis of Lignocellulosic Medical Waste in a Fixed Bed Reactor - Okekunle, Pious O.; Itabiyi, Olukunle E.; Olafimihan, Emmanuel O.; Adetola, Sunday O.; Oyetunji, Oluremilekun R.; Hamsat, Kayode A.; Olowolagba, Dayo E.; Falomo, Olalekan M. (European Scientific Journal, ESJ, 2019)
The lethargic modes of medical waste disposal in many developing countries have been a cause of concern to many regulatory agencies. In this study, effect of reactor temperature on pyrolysis of lignocellulosic medical waste in a fixed bed reactor was investigated. Gauze bandage was procured from AKOL Pharmacy, Ogbomoso, South-Western Nigeria. Samples of the gauze bandage, 40 g each at a time, were fed into a retort and the retort inserted into a developed fixed bed reactor for pyrolysis at different temperatures (300, 400, 500 and 600 oC) with a residence time of 15 minutes. Tar, gas and char yields were weighed using an electronic balance (WT20002T, RS232C) and were further expressed in percentage of the initial weight of the sample. Results showed that tar and gas yields increased with increasing reactor temperature while char yield decreased with it. Both intraand extra-particle secondary reactions were insignificant and therefore could not influence the yield spectra of products. The highest yield of tar, gas and char were 52.08, 28.42 and 52.7%, respectively while the lowest yield were respectively 30.50, 16.80 and 19.50%. Lignocellulosic medical waste can be a viable source of biofuels and raw materials respectively for sustainable development and for chemical industries.